2003
DOI: 10.1111/1467-9566.00329
|View full text |Cite
|
Sign up to set email alerts
|

Representing childhood cancer: accounts from newspapers and parents

Abstract: We present an analysis of newspaper accounts and parents' accounts of childhood cancer. Newspaper accounts construct cancer as a threat to the entitlements and category-bound activities of childhood. Newspaper discourses around children with cancer are predominantly eulogising, constructing children as courageous, stoical and inspirational. Parents are characterised as confederates in the 'battle' against cancer; as fund-raisers; and as guardians of their children's identities. Little attention is given to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
1
27
0
3
Order By: Relevance
“…O impacto da doença faz com que cada membro da família desenvolva novas habilidades e tarefas no cotidiano familiar para resolver os conflitos em função da hospitalização e das demandas da doença nos aspectos físicos, psicossociais e financeiros. [1][2] Quando uma criança tem o diagnóstico de câncer, é frequente a mãe aprender rapidamente a lidar com os aspectos médicos da doença e com as necessidades e medo dos membros da família. Assim, ela é vista como a principal pessoa no cuidado da criança doente.…”
Section: Introductionunclassified
“…O impacto da doença faz com que cada membro da família desenvolva novas habilidades e tarefas no cotidiano familiar para resolver os conflitos em função da hospitalização e das demandas da doença nos aspectos físicos, psicossociais e financeiros. [1][2] Quando uma criança tem o diagnóstico de câncer, é frequente a mãe aprender rapidamente a lidar com os aspectos médicos da doença e com as necessidades e medo dos membros da família. Assim, ela é vista como a principal pessoa no cuidado da criança doente.…”
Section: Introductionunclassified
“…This is similar in many ways to the idealized portrayal of childhood cancer survivors in news media [10,11,48]. Researchers have found that the discourse around children with cancer in newspaper articles is primarily "eulogizing, constructing children as courageous, stoical and inspirational" [10].…”
Section: Discussion/conclusionmentioning
confidence: 76%
“…In this way, news helps to shape the social and cultural contexts within which illness and disease are both collec-what having it is like and how it might be cured. For example, newspaper accounts of children with cancer have been found to be primarily eulogizing, with children portrayed only as heroic, stoic, and inspirational [10,11]. In this way, news media help to define the boundaries for lay understanding of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our 22 analysis suggests that it is misleading to imagine that these are the only institutions involved in processes of commodification. In contemporary society, mass media play a significant role in filtering and shaping the reporting of science, health and medicine (Seale, 2003). Media reporting of child organ retention scandals in the UK in recent years has made an independent contribution to the commodification of body parts, recruiting them for use in the manufacture of a media scandal.…”
Section: Discussionmentioning
confidence: 99%
“…Children in today's society are treated as being of particular social value, and so stories of their mistreatment are unusually attractive to journalists (Franklin and Tutton, 2001), as are stories that appear to violate or spoil the apparent "innocence" of childhood (Dixon-Woods et al, 2005), though idealised media accounts of childhood may be very different from the accounts given by family members to social researchers (Dixon-Woods et al, 2003).…”
Section: Discussionmentioning
confidence: 99%